2014
DOI: 10.1590/s1516-89132014000200019
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerol from biodiesel industry as substrate for biosurfactant production by Bacillus subtilis ATCC 6633

Abstract: Glycerol, a co-product of the biodiesel industry, may be a suitable raw material for the production of high addedvalue compounds by the microorganisms. This study aimed to use the glycerol obtained from the biodiesel production process as the main carbon source for biosurfactant production by Bacillus subtilis ATCC 6633. Results indicated that the strain lowered the surface tension of the cell-free fermented broth to 31.5 ± 1.6 mN/m, indicating the production of biosurfactant. The critical micelle concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
2
13
0
2
Order By: Relevance
“…This obviously indicates that in both cases good biosurfactant production and recovery was obtained. For both culture media (AGG and CGBP), the ST remained constant ≈ 34 mN/m, after 24 h, which is similar to reported by Sousa et al [5] 31.5 mN/m after 72 h of fermentation. In this sense, CMD-2 remained also constant ≈ 72 mN/m data.…”
Section: Measurement Of Surface Activity -Collapsed Foam and Culture supporting
confidence: 88%
See 3 more Smart Citations
“…This obviously indicates that in both cases good biosurfactant production and recovery was obtained. For both culture media (AGG and CGBP), the ST remained constant ≈ 34 mN/m, after 24 h, which is similar to reported by Sousa et al [5] 31.5 mN/m after 72 h of fermentation. In this sense, CMD-2 remained also constant ≈ 72 mN/m data.…”
Section: Measurement Of Surface Activity -Collapsed Foam and Culture supporting
confidence: 88%
“…The literature describes the production of surfactin per liter of culture medium (glucose as carbon source and extracted direct from the culture medium) to be at least 500 mg/L, whereas using glycerol as carbon source, lower yields are usually described (158.14 mg/L after 72 h of fermentation) [5], [19][20]. The production with AGG medium was ≈ 325 mg of surfactin/liter of culture medium, whereas with the CGBP medium was 71 mg/L.…”
Section: Measurement Of Surface Activity -Collapsed Foam and Culture mentioning
confidence: 99%
See 2 more Smart Citations
“…The absorption peaks were similar to those observed by Jara, Andrade, and Campos-Takaki (2013) and Sousa et al (2014) when characterizing a tensoactive agent produced by Geobacillus stearothermophilus and a biosurfactant produced by B. subtilis, respectively. Camacho-Chab et al (2013) studying the genus Microbacterium isolated from marine environment reported the production of glycoproteins able to emulsify aromatic hydrocarbons and oils.…”
Section: Bacterial Strain Investigated For the Production Of Biosurfasupporting
confidence: 85%